The Effectiveness of an Individual Approach and A Comprehensive Assistance System in The Prevention of Female Crime (International Journal of Scientific Trends, 2026)
This article discusses the effectiveness of an individual approach and a comprehensive assistance system in the prevention of female crime. In addition, the author reveals the distinctive aspects between the concepts of prevention and deterrence of female criminality. The article also presents proposals and recommendations aimed at increasing the effectiveness of an individual approach and a comprehensive support system in preventing crimes committed by women.